Упрастите выражение: 1) -2,4а×(-5b); 2) 9a-a-8b+3b; 3) a+(a-10)-(15+a); 4) -4(b-4)+7(b+2).

даша3649 даша3649    1   13.04.2020 20:51    0

Ответы
1207malinap0c23p 1207malinap0c23p  30.07.2020 12:07

Пошаговое объяснение:

1) -2,4а * (-5b) =

= (-2,4 * (-5)) ab =

= 12ab

2) 9a - a -8b +3b =

=(9a-a) + (-8b+3b) =

=8a -(8b-3b) =

= 8a -5b

3) a+(a-10)-(15+a) =

= a+a-10-15-a =

= (а +а -а ) + (-10 + (-15)) =

= а -(10+15) =

= a - 25

4) -4(b-4) +7(b+2) =

= -4b +16 +7b +14 =

= (7b-4b) + (16+14)=

=3b +30 =

можно еще вынести общий множитель:

=3(b+10)

ПОКАЗАТЬ ОТВЕТЫ
PRO11116 PRO11116  30.07.2020 12:07

1) 12ab;

2) 8a-5b;

3) a-25;

4) -4b+16+7b+14=3b+30

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика